The effects of using different bitumen modifiers and hydrated lime together on the properties of hot mix asphalts - Yilmaz, Mehmet; Yalcin, Erkut (Taylor & Francis Ltd, 2016)
In this study, the effects of styrene-butadiene-styrene (SBS), American gilsonite (AG) and Iranian gilsonite (IG) usage in bitumen modification, and hydrated lime usage in mixture modification on the performance of hot mix asphalts (HMAs) were investigated. For bitumen modification, 4.0% SBS, 11.0% AG and 10.0% IG were used with respect to bitumen weight. Hydrated lime was used as filler in proportion of 2% with respect to aggregate weight. It was determined that the high temperature properties of bituminous binders were improved with bitumen additive usage. Marshall stability and flow, resistance to moisture-induced damage, indirect tensile stiffness modulus and wheel-tracking tests were applied to the mixtures. The mixture experiments revealed that both HMAs stability and stiffness and also resistance to moisture damage and wheel tracking were increased by hydrated lime and binder additives usage. It was observed that the hydrated lime was not as effective as the binder additives and the most effective additive was usually AG in terms of stability, stiffness and wheel tracking. It was detected that the SBS was the most effective additive for resistance to moisture-induced damage.
Keywords: hot mix asphalt; modification; gilsonite; hydrated lime; styrene-butadiene-styrene